Criteria for students with disabilities regarding the curricular adjustment plan in undergraduate courses, University of Costa Rica - Abarca Rodríguez, Allan (2025)
Introduction: This article addresses the results of a study in which undergraduate students with disabilities at the University of Costa Rica (UCR) were surveyed regarding their satisfaction with an accommodation plan that provides them with support, in the form of non-significant accommodations, in university courses. Objective: The objectives developed for this article are: a) to compare the agreed-upon adaptation plan with the needs expressed by the student population during the negotiation process with academic authorities, and b) to determine compliance with the agreed-upon and executed adaptation plan, from the students' perspective, once the course has concluded. Method and technique: A structured interview was conducted with a student population that agreed to and implemented an adaptation plan, for which a structured questionnaire was administered. Through a snowball sampling method, 14 students are selected and asked about their experience in 5 randomly chosen courses, for a total of 70 courses analyzed. Results: Students are highly satisfied with the agreed-upon adjustments and inclusive classroom treatment, although nearly half of the courses studied experienced failure to implement the agreements. [Continue reading in the article]